Impacts of knowledge sharing and knowledge creation on employee engagement - case studies of Malaysian universities - Sui, Hai Juan (2017)
Employee engagement is increasingly important in this competitive society because organizational competitiveness requires knowledge especially the tacit knowledge which resides in employees and it cannot be achieved unless employees are engaged in the processes of managing knowledge. However, studies on employee engagement from the perspective of knowledge management practice are rare. The main purpose of this study is to assess the impacts of knowledge sharing and knowledge creation on employee engagement. After identifying knowledge sharing and knowledge creation could facilitate employee engagement, the study developed a model that presents knowledge sharing and knowledge creation towards employee engagement. This study adapted quantitative research method employing questionnaire to collect data from academic staff in a public and a private universities located in Malaysia. A sample of 303 academic staff were selected using stratified sampling method from a population of 1162. Data were analysed using SPSS. Descriptive analysis, testing for normality, reliability test, validity test, t-test and correlation analysis, as well as linear regression analysis were performed. The results show that three dimensions of knowledge sharing (i.e. structural, relational and cognitive) have positive and significant impact on employee engagement; and also two dimensions of knowledge creation (i.e. exploration and exploitation) positively and significantly affect employee engagement. From a practical contribution perspective, this could aid universities to better utilize the knowledge management practices to engage employees, so that to attain and sustain competitive advantage. It is recommended that the proposed model could be further enriched by adding other knowledge management practices.